TINGKAT ADOPSI ALUMNI PROGRAM P4S (PUSAT PELATIHAN PERTANIAN PEDESAAN SWADAYA) TERHADAP TEKNOLOGI BUDIDAYAIKAN DALAM KERAMBA JARING APUNG DI KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Yulia S Haryati Pratiwi; Kusai '; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The survey was conducted on February 19 to 28, 2015 in the sub-district of Kampar Riau Province. This study purposive survey method. Some farmers Graduated from P4S in Kampar district is 28 people and whole of them to be respondents by census. The purpose of this study was to collect and analyze information on: characteristics of fish farmers in cages aquaculture both internal and external, to measure adoption level of fish farming in floating cages, to analyze the relationship between the farmer characteristic with adoption by using coefficient rank Spearman correlation. The adoption level of farmer in the Kampar district for cager aquaculture in the middle category, and the pace of implementation of the recommended technology packages are in the medium category, because not all technology package recommended applied by the expansion of the farmers, because innovation is advisable nature difficult to implement. The recommended technology package is the choice of the location and layout, the design of the cage, the cleanliness of the facilities and equipment, seeds, feed, fish diseases and pests, harvest. Keyword : Adoption level, Graduated, Aquaculture Technology